Effects of deep heating modalities on the morphological and elastic properties of the non-insertional region of achilles tendon: a pilot study. (31st December 2022) - Munari, Daniele; Serina, Anna; Leonardelli, Arianna; Lanza, Davide; Caramori, Alberto; Guerrini, Andrea; Angela, Modenese; Filippetti, Mirko; Smania, Nicola; Picelli, Alessandro
Abstract: Background: Over the last 20 years, both diathermy and ultrasound have been popular choices for many clinicians in treating musculoskeletal disorders. However, there is a lack of clinical evidence of deep heating modalities to treat tendon pathology, There is no study to investigate the effects of such as physical modalities on morphological and elastic properties on the human tendons. Objective: the objective of the present study was to compare the effects of diathermy and ultrasound therapies on cross sectional area, transversal height and hardness percentage of the non-insertional region of the Achilles tendon in able-bodied subjects. Methods: healthy volunteers were divided in diathermy and ultrasound group received six 15-min treatment sessions. Before and after treatment a sonographic assessment was conducted by mean of ultrasonography and the following parameters were recorded: cross sectional area, transversal height and hardness percentage. Results: thirty-two subjects were enrolled. Between-group comparisons showed a significant change on hardness percentage ( p = 0.004) after treatment in diathermy therapy group. Within-group comparison showed a significant improvement in the hardness percentage for the diathermy ( p = 0.001) and ultrasound ( p = 0.046) after two weeks of treatment. Conclusion: this pilot study demonstrated larger effects on morphological and elastic properties of the non-insertional region of the Achilles tendon after diathermy than ultrasound therapy in normal tendons. Diathermy may be a useful deep heat modality for treating non-insertional Achilles tendinopathy.